IMPLEMENTASI SUPERVISI AKADEMIK HUMANIS UNTUK MENINGKATKAN KOMPETENSI PEDAGOGIK GURU DI PONDOK PESANTREN AL MAHMUD AL ISLAMY AIK AMPAT GERUNG LOMBOK BARAT NUSA TENGGARA BARAT - Isnadia, Novi (UNISAN JURNAL, 2025)
This study aims to describe the implementation of humanistic academic supervision in improving teachers’ pedagogical competence at Pondok Pesantren Al Mahmud Al Islamy, Aik Ampat, Gerung, West Lombok. The study is motivated by the fact that many educational institutions still apply administrative and intimidating forms of supervision, which often fail to provide meaningful professional development for teachers. Humanistic supervision emerges as an alternative approach that emphasizes empathetic communication, respect for teachers, and dialogic professional guidance. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, classroom observations, reflective discussions, and documentation analysis, and then analyzed using Miles and Huberman’s interactive model. The findings indicate that humanistic academic supervision is implemented through several stages, including building positive interpersonal relationships, conducting non-threatening classroom observations, appreciating teachers’ strengths, and providing constructive feedback through collegial dialogue. Teachers responded positively to this approach, becoming more open, valued, and willing to reflect on their teaching practices. The implementation of humanistic supervision was proven to enhance teachers’ pedagogical competence in lesson planning, active learning implementation, classroom management, and authentic assessment. Furthermore, it helped increase teachers’ intrinsic motivation, confidence, and creativity. The study concludes that humanistic academic supervision is an effective and relevant approach for Islamic boarding schools. This approach not only strengthens teachers’ professionalism but is also aligned with Islamic educational values emphasizing compassion, consultation, and character development. Humanistic supervision is recommended as a sustainable model for teacher development to improve instructional quality.